The kinetics of humoral response and its relationship with the disease severity in COVID-19 - Lili Ren (Nature Portfolio, 2020)
Lili Ren et al. investigate antibody response from 176 COVID-19 patients who presented different stages of their disease. This study suggests the late onset of antibody response as a risk factor for disease severity and a limited role of antibody titers in predicting the disease severity of COVID-19.